2020
DOI: 10.1371/journal.pone.0227356
|View full text |Cite
|
Sign up to set email alerts
|

An updated evaluation of serum sHER2, CA15.3, and CEA levels as biomarkers for the response of patients with metastatic breast cancer to trastuzumab-based therapies

Abstract: Background The transmembrane receptor tyrosine kinase HER2 is overexpressed in approximately 15% of breast tumors and correlates with poor clinical prognosis. Several treatments that target HER2 are approved for treatment of HER2-positive metastatic breast cancer. The serum biomarkers most widely used to monitor anti-HER2 therapies in patients with HER2-positive metastatic breast cancer currently are CA15.3 and CEA. Nevertheless, their clinical utility in patients with breast cancer remains a subject of discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Patients in the benign group and control group were pathologically diagnosed to exclude malignant lesions and had normal communication skills. All breast cancer patients met the following inclusion criteria: (1) the patients were diagnosed with breast cancer after pathological examination [ 11 ]; (2) the patients had not received related treatment before enrollment; (3) the patients had complete clinical data. Exclusion criteria were as follows: (1) the patients could not communicate with others due to hearing disorder, language disorder, and other factors; (2) the patients had distant metastasis of cancer cells; (3) the patients had received treatment measures such as chemotherapy and radio therapy; (4) the patients were complicated or had been complicated with other malignant tumors; (5) the patients were complicated with hematological diseases, autoimmune diseases, and infectious diseases; (6) the patients had dysfunction of important organs; (7) pregnant or lactating women.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in the benign group and control group were pathologically diagnosed to exclude malignant lesions and had normal communication skills. All breast cancer patients met the following inclusion criteria: (1) the patients were diagnosed with breast cancer after pathological examination [ 11 ]; (2) the patients had not received related treatment before enrollment; (3) the patients had complete clinical data. Exclusion criteria were as follows: (1) the patients could not communicate with others due to hearing disorder, language disorder, and other factors; (2) the patients had distant metastasis of cancer cells; (3) the patients had received treatment measures such as chemotherapy and radio therapy; (4) the patients were complicated or had been complicated with other malignant tumors; (5) the patients were complicated with hematological diseases, autoimmune diseases, and infectious diseases; (6) the patients had dysfunction of important organs; (7) pregnant or lactating women.…”
Section: Methodsmentioning
confidence: 99%
“…MUC1 can be a marker for BC diagnosis because its expression is significantly higher in cancer tissue than in normal tissue [ 137 ]. Indeed, the measurement of CA 15.3 can be useful in predicting response to trastuzumab [ 138 ]. The assay of sMUC1 was approved by FDA for disease monitoring in BC patients [ 45 ].…”
Section: Trastuzumab-mechanisms Of Actionmentioning
confidence: 99%
“…The assay of sMUC1 was approved by FDA for disease monitoring in BC patients [ 45 ]. Several studies demonstrate that the elevated level of CA 15.3 in serum is significantly correlated with tumor size and metastasis in BC patients [ 138 ].…”
Section: Trastuzumab-mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 The HER2 extracellular domain (ECD), the target antigen for current anti-HER2 mAb therapies such as trastuzumab and pertuzumab, is comprised of four subdomains (I–IV) and can be cleaved from the surface of breast cancer cells by extracellular-matrix degrading matrix metalloproteases (MMPs). 44–46 A growing body of literature has demonstrated that a reduction in HER2 ECD concentrations in patient serum during therapy is predictive of pathologic complete response (pCR) and improved outcomes 7 , 47–51 while rising or refractory serum HER2 ECD levels indicate resistance to therapy and the need for alternative treatments. 35 While the therapeutic binding domains of trastuzumab and pertuzumab have been characterized as within subdomain IV and subdomain II ( Figure 2 ), 52 respectively, commercially available ELISAs utilize antibodies that often bind to undefined or undisclosed epitopes on the HER2 ECD.…”
Section: Domain-specific Targeting For Elisa Antibodies To Prevent Interferencementioning
confidence: 99%